Clinicopathological features, treatment patterns, and survival outcomes among Syrian patients with advanced breast cancer - Muhammad, Muhammad; Alali, Mousa; Saifo, Maher (Frontiers in Oncology, 2024)
BackgroundAdvanced breast cancer (ABC) is a heterogeneous disease with varied prognoses, that is affected by many clinicopathological features. This study aimed to investigate the clinicopathological characteristics, first-line treatment (FLx), and prognostic impact of these features on survival among Syrian patients with ABC.Materials and methodsThis retrospective cohort study included patients with ABC. The association of clinicopathological factors with survival was assessed using Kaplan-Meier curves and the log-rank test, as well as the Cox proportional hazards regression model to calculate the hazard ratio (HaR).ResultsA total of 423 patients with ABC were included in the study, with a median age (range) of 47 years (23-82). 83% of metastases were metachronous. Most patients (91.8%) received chemotherapy as the FLx. The median progression-free survival (PFS) and overall survival (OS) of all the patients were 7 and 16 months, respectively. The median PFS was associated with four factors, which were time of metastasis (adjusted HaR=1.861, 95% CI 1.420-2.438, P<0.0001), performance status (PS) (adjusted HaR=1.456, 95% CI 1.049-2.021, P=0.025), ovarian metastasis (adjusted HaR=7.907, 95% CI 1.049-59.576, P=0.045), and FLx (adjusted HaR=2.536, 95% CI 1.581-4.068, P<0.0001). Similarly, the OS was associated with three factors, including hormone receptors (HRs) status (adjusted HaR=1.124, 95% CI 1.009-1.252, P=0.034), time of metastasis (adjusted HaR=2.099, 95% CI 1.588-2.775, P<0.0001), and PS (adjusted HaR=1.787, 95% CI 1.429-2.233, P<0.0001). In the HR-positive/human epidermal growth receptor 2 (HER2)-negative group, endocrine therapy was significantly associated with longer PFS compared with chemotherapy (15 vs 7 months, adjusted HaR=2.699, 95% CI 1.417-5.143, P=0.003). Furthermore, there was no difference in OS between the two treatment modalities (P=0.855).ConclusionsABC survival varies depending on the location of metastases. Good PS and synchronous stage 4 disease were independent prognostic factors for longer PFS and OS. In the HR-positive/HER2-negative group, PFS for endocrine therapy was significantly longer than chemotherapy, with no differences in OS. This study confirms that endocrine therapy is preferred as an FLx for ABC in the HR-positive/HER2-negative group.